Evaluation of Acidic Ionic Liquids as Catalysts for Furfural Production from Eucalyptus nitens Wood - Lucía Penín; Mar López; Valentín Santos; Juan Carlos Parajó (Molecules, 2022)
Eucalyptus nitens wood samples were subjected to hydrothermal processing to obtain soluble saccharides from the hemicellulosic fraction. The hemicellulose-derived saccharides were employed as substrates for furfural production in biphasic media made up of water, methyl isobutyl ketone, and one acidic ionic liquid (1-butyl-3-methylimidazolium hydrogen sulfate or 1-(3-sulfopropyl)-3-methylimidazolium hydrogen sulfate). The reactions were carried out in a microwave-heated reactor to assess the effects of the most influential variables. Under selected operational conditions, the molar conversions of the precursors into furfural were within the range of 77–86%. The catalysts conserved their activity after reutilization in five consecutive reaction cycles.